Positive solutions for a semipositone nonlocal discrete boundary value problem. (June 2019) - Luca, Rodica
Abstract: We investigate the existence of positive solutions for a system of nonlinear second-order difference equations with a parameter and a sign-changing nonlinearity, subject to multi-point boundary conditions. In the proof of our main results we apply the nonlinear alternative of Leray–Schauder type and the Guo–Krasnosel'skii fixed point theorem.